(3cJGH eYQaI eSGMI GdCTcGd GdHSjWI hGdcQjIs - ((3Hfj ehSi (B( (3eMeO hGdMSf hCMeOs
(3ChdgG (B:s
(3GdWhd Chd GdCbOGQ GdJi JeO GdCTcGd hgh eG GeJO Ydi GSJbGeI aEPG GeJO GdSWM GYJQGVkG ai MjR GdWhd aPdc GdCSJOGQ s
(3BNQgG (B:s
(3dPdc VQH eQHY M W ai eQHY g` M GdeSGhi dVQH g` W ai W H ai H g` ai g` L eSGhjkG deQHY VQH OW g` M hPdc eG CQOfG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS YTQs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1458s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs